Prospective study on outcome and advantage of primary skin grafting in cases of avulsion scalp injury following trauma - Tripati, Neeraj; Singh, Mayank; Singh, Rahul; Devan, Maha; Chauhan, Anchal; Tripati, Shashank; Chandra, Dhruv; Singh, Anil Kumar; Singh, Pradeep Kumar; Sahi, Hanuman Prasad; Singh, Aryendra; Kumar, Ashish; et al. (International Surgery Journal, 2020)
Background: Traumatic avulsion injury poses severe risk as the overlying protective covering is lost and the raw tissue is exposed to the environment. Avulsion injuries involving the scalp are even more complicated to treat because of significant cosmetic concern involved. Aim of the study was to find a better solution than the existing method, we conducted a prospective study involving 13 patients with isolated traumatic scalp avulsion injury. Methods: This prospective study was conducted in Motilal Nehru Medical College and associated Swaroop Rani Nehru Hospital, Prayagraj, after taking written and informed consents from the patients, between June 2017 and June 2019.These were divided into two groups (A and B) based on whether the underlying periosteum was intact or not. Results: Patients with intact periosteum (Group A) underwent primary thin thickness skin grafting within a few hours of their admission while the other group (Group B) was treated with a traditional conservative approach. We compared the results of both the groups and found that Group A patients not only had satisfactory graft uptake (≥85 TBSA) but also had significant decreased risk of infection, lesser hospital stay, overall decreased healthcare cost, better cosmoses and early return to routine activity. Conclusions: For the surgeon, this single step procedure is safe and technically easy. Thus this approach was found to be superior than the current traditional approach.